2023
DOI: 10.1097/mlr.0000000000001805
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Care and Urinary Tract Infection Management

Abstract: Background: During the COVID-19 pandemic, more health care issues were being managed remotely. Urinary tract infections (UTIs) are being managed more often using telehealth although few reports compare the rate of UTI ancillary service orders placed and fulfilled during these visits. Objectives: We aimed to evaluate and compare the rate of ancillary service orders and order fulfillments in incident UTI diagnoses between virtual and in-person encounters. Research Design: The retrospective cohort study invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…In other studies, we found that order likelihood is lower for virtual than for in-person visits. 16,17 In this study, we found that 3 moderators that might influence patient treatment adherence did little to account for fulfillment disparities by visit mode.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…In other studies, we found that order likelihood is lower for virtual than for in-person visits. 16,17 In this study, we found that 3 moderators that might influence patient treatment adherence did little to account for fulfillment disparities by visit mode.…”
Section: Resultsmentioning
confidence: 55%
“…16 An incident UTI visit was similarly defined, except the interval between visits was set at 90 days. 17…”
Section: Study Samplementioning
confidence: 99%
See 2 more Smart Citations
“…The KP research studies also tackle new areas in telemedicine research by comparing the impact of telemedicine and in-person visits on ancillary services utilization, including medication, laboratories, and imaging, for urinary tract infections7 neck and back pain,8 and depression 9. These studies found that although ancillary service orders resulting from telemedicine visits were generally high, orders from telemedicine encounters were not placed as often as in-person encounters for urinary tract infections, 7 neck and back pain, 8 but there were no significant changes in patient fulfillment of ordered antidepressant medications 9. The KP findings highlight the importance of prior use of mail-order pharmacy options in promoting the fulfillment of prescribed medication orders, irrespective of visit mode 10.…”
Section: Commentarymentioning
confidence: 99%